Pelatihan Penyediaan Sabun Cuci Tangan Cair Bagi Warga RT 02 Dusun Rewulu Wetan, Godean, Yogyakarta - Purwanti, Ani; Yusuf, Muhammad (DHARMA BAKTI, 2022)
The Covid-19 pandemic has been going on since 2020. Efforts to improve health protocols are still being echoed. Washing hands with soap has become a new habit during this pandemic. There are many hand washing liquid soaps on the market, but it is relatively expensive. We need to find an effort to be able to get liquid soap at an economical price. This can be done by making your own hand washing liquid soap. Fulfilling the need for liquid hand washing soap is also important for residents of RT 02 in Rewulu Wetan, Sidokarto, Godean. Therefore, on March 28, 2021, a training was held on making hand-washing liquid soap for the residents of the hamlet. This training activity is to increase the knowledge of residents of RT 02, Rewulu Wetan about liquid hand soap and how to make it. Another goal is to get a cheaper liquid soap when compared to products on the market. This activity is expected to be a source of inspiration for participants to become entrepreneurs. The training was carried out by presenting the material by the resource persons. The activity continued with the practice of making liquid hand soap. The training closed with a discussion session with the trainees. The implementation of the training can run well and smoothly. The residents who attended were enthusiastic about receiving the material presented. This could be seen from the discussion about the training materials. The result of this training is an economical liquid hand soap.